Global, regional and national burden of drug use disorders, 1990–2021: decomposition analysis, health inequality analysis and predictions to 2035 - Jin, Ruiying; Zhang, Shenyu; Xiong, Jun; Liu, Baixi (Frontiers in Public Health, 2025)
BackgroundDrug use disorders (DUDs), a significant public health issue worldwide, encompass disorders related to sedatives, cannabis, opioids, heroin, hallucinogens, club drugs, and inhalants. This study examines the changes in the global burden of DUDs from 1990 to 2021, aiming to provide a scientific foundation for strategies to mitigate the harms associated with substance abuse.MethodsThe study utilized Global Burden of Disease (GBD) 2021 data to analyze trends in the incidence, prevalence, mortality, disability-adjusted life years (DALYs) associated with DUDs through Socio-demographic Index (SDI), attributable risk factors, and EAPC. Decomposition analysis was employed to assess the impact of age, gender, and SDI on the burden of DUDs, while the inequality distribution of DALYs was examined using the inequality slope index (SII) and the concentration index (CI).ResultsOpioid use disorder accounted for the highest age-standardized disability rates (ASDR) and age-standardized mortality rates (ASMR) among the five drug use disorders, while cannabis use disorder is the leading cause of Age-standardized prevalence rates (ASPR). The Age-standardized incidence rates (ASIR) of opioid use disorder has demonstrated a downward trend, whereas both ASPR and ASMR have shown an increase; notably, the ASIR for opioid use disorder has declined the least among the five drug use disorders. The burden of DUDs in high SDI areas is significantly greater than that in low SDI areas, with income inequality exacerbating the uneven distribution of DALYs. The primary attributable risk factors are drug use and behavioral risks. While the ASIR of opioid use disorder is increasing, while others are experiencing a decline. The burden of DUDs varies among the five drug use disorders due to factors such as population aging, population changes, and age distribution.ConclusionThe findings reveal absolute and relative inequalities in DALYs associated with drug use disorders, which are concentrated in high-income regions.